2007
DOI: 10.1037/1064-1297.15.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost contingency management in community clinics: Delivering incentives partially in group therapy.

Abstract: This study examined the feasibility and effectiveness of prize-based contingency management (CM) when incentives for attendance were administered in group therapy and incentives for abstinence were administered in individual meetings. Three community substance abuse treatment programs participated in this two-phase, crossover design study. Outpatients (N = 103) entering treatment who met diagnostic criteria for cocaine, opiate, and alcohol abuse or dependence were recruited. During the standard condition, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…Many studies have evaluated post-intervention effects of CM on substance use months after external reinforcement ceases, but most are underpowered to detect long term changes. Although meta-analyses find effects of CM are not sustained at long term follow-ups (Benishek et al, 2014; Prendergast et al, 2006), an increasing number of studies demonstrate benefits of CM months after treatment ends (Alessi, Hanson, Wieners, & Petry 2007; Carroll et al, 2016; Halpern et al, 2015; Higgins et al, 2000, 2007; Higgins, Heil, & Lussier 2004; Kadden, Litt, Kabela-Cormier, & Petry 2007; Kendzor et al, 2015; McDonell et al, 2013; McKay et al, 2010; Petitjean et al, 2014; Petry, Andrade, Barry, & Byrne 2013c; Petry, Alessi, Byrne, & White 2015b; Petry & Martin 2002; Petry et al, 2005c; Reback et al, 2010; Roll, Chudzynski, Cameron, Howell, & McPherson 2013; Secades-Villa et al, 2011; Secades-Villa, Garcia-Rodriguez, Lopez-Nunez, Alonso-Perez, & Fernandez-Hermida 2014; Schottenfeld, Moore, & Pantalon 2011; Winhusen et al, 2014). A recent review (Davis et al, 2016) reported that 29% of studies that evaluated long-term effects of CM found that it retained significant benefits even after reinforcers were no longer delivered.…”
Section: Concerns About CMmentioning
confidence: 99%
“…Many studies have evaluated post-intervention effects of CM on substance use months after external reinforcement ceases, but most are underpowered to detect long term changes. Although meta-analyses find effects of CM are not sustained at long term follow-ups (Benishek et al, 2014; Prendergast et al, 2006), an increasing number of studies demonstrate benefits of CM months after treatment ends (Alessi, Hanson, Wieners, & Petry 2007; Carroll et al, 2016; Halpern et al, 2015; Higgins et al, 2000, 2007; Higgins, Heil, & Lussier 2004; Kadden, Litt, Kabela-Cormier, & Petry 2007; Kendzor et al, 2015; McDonell et al, 2013; McKay et al, 2010; Petitjean et al, 2014; Petry, Andrade, Barry, & Byrne 2013c; Petry, Alessi, Byrne, & White 2015b; Petry & Martin 2002; Petry et al, 2005c; Reback et al, 2010; Roll, Chudzynski, Cameron, Howell, & McPherson 2013; Secades-Villa et al, 2011; Secades-Villa, Garcia-Rodriguez, Lopez-Nunez, Alonso-Perez, & Fernandez-Hermida 2014; Schottenfeld, Moore, & Pantalon 2011; Winhusen et al, 2014). A recent review (Davis et al, 2016) reported that 29% of studies that evaluated long-term effects of CM found that it retained significant benefits even after reinforcers were no longer delivered.…”
Section: Concerns About CMmentioning
confidence: 99%
“…Nonetheless, several studies indicate that contingency management procedures may effectively reduce excessive alcohol use (e.g., Alessi et al, 2007; Alessi and Petry, 2013; Barnett et al, 2011; Hagedorn et al, 2013; Hunt and Azrin, 1973; Kaffarnus et al, 2011; McDonell et al, 2012; Miller, 1975; Miller et al, 1974a, 1974b; Petry et al, 2000, 2005b). However, to verify abstinence, most studies measured overt signs of intoxication, BAC, and/or BrAC at intervals ranging from daily to once a week.…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, CM shows similar rates of relapse to various other SUD therapies. Some studies, however, do find persistent effects of CM post intervention (e.g., Alessi, Hanson, Wieners, & Petry, 2007; Dougherty et al, 2015; Higgins, Badger, & Budney, 2000; Higgins, Wong, et al, 2000; Petry, Martin, & Simcic, 2005; Petry & Martin, 2002). Investigation of factors that promote sustained effects will be important moving forward as will identification of behavioral, neurocognitive and environmental markers that are associated with and predictive of long-term treatment outcomes.…”
Section: Introductionmentioning
confidence: 98%